Global and culturally diverse leaders and leadership : new dimension and challenges for business, education and society - Chin, Jean Lau; Trimble, Joseph E.; Garcia, Joseph E. (Building leadership bridges,, 2017)
Global and Culturally Diverse Leaders and Leadership explores diverse cultural leadership styles and paradigms that are dynamic, complex, globally authentic and culturally competent for the 21st century. An outstanding group of scholars considers how the different worldviews and lived experiences of leaders influence their leadership styles. They discuss several dimensions, models and initiatives for examining leadership in a global and diverse world, ultimately offering ways in which these leadership processes may be assessed and cultivated in a culturally sensitive and ecologically valid manner. Redefining leadership as global and diverse, this book imparts a new understanding of the criteria for selecting, training and evaluating leaders in the 21st century.